"Acceptability" in the Translation into Malay of Rihlat Ibn Battutah (KEMANUSIAAN The Asian Journal of Humanities, 2012)
This article reports on a descriptive study of the translation of the Arabic travel literature of Rihlat Ibn Battutah into the Malay language. The study investigated the concept of acceptability in the translation of cultural elements such as food/drink, clothing and religious items found in the 14th century text in its modern Malay translation Pengembaraan Ibn Battutah. The data in the source text (ST) were selected and mapped to the corresponding elements in the target text (TT) using the descriptive translation studies (DTS) methodology. A manual analysis of the ST and TT pairs based on a methodological modification of the taxonomy of Vinay and Darbelnet was then carried out. The findings of the study provides initial guidelines for Arabic-Malay translations of cultural words.